PENGARUH CORPORATE SOCIAL RESPONSIBILITY , RETURN ON ASSET (ROA), CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN (PBV) ( Studi Empiris Pada Perusahaan Sub Sektor Perdagangan Besar Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Heni Yusnita (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to determine and analyze the effect of Corporate Social Responsibility, Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER) Â on Firm Value (PBV) for the 2018-2021 period. The population in this study were 47 companies in the large trading subsector for the 2018-2021 period. Based on the sampling technique using purposive sampling, 12 companies met the criteria. Data collection techniques use documentation from financial reports published on the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The data analysis technique used is simple linear regression analysis. The type of research used is quantitative. The program used for data processing is SPSS version 23. The results of this study indicate that: Corporate Social Responsibility has an effect on firm value (PBV), Return on Assets (ROA) has an effect on firm value (PBV),Current Ratio (CR) has an effect on firm value (PBV), Debt to Equity Ratio (DER) has an effect on firm value (PBV).